Personality and political preferences: the 2016 U.S. presidential election - Abe, Jo Ann A (Journal of Research in Personality, 2018)
This study examined whether personality variables would account for political preferences during the 2016 U.S. Presidential Election using a demographically diverse sample of participants (N = 897). Study A revealed participants' ratings of their own personality and emotions were weakly associated with political preferences, but their ratings of candidates' personality showed robust associations, and were far more predictive of voting intention than all of the demographic variables, political affiliation, and racial attitudes combined. In Study B, linguistic analysis of narratives revealed words reflective of liberal values were correlated with positive evaluations of Clinton's personality, whereas words reflective of conservative values and “populist” sentiment were correlated with positive evaluations of Trump's personality, suggesting appraisals of candidates may be associated with values. (C) 2018 Elsevier Inc. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-761-611-227-871 tex.type: [object Object]
Keywords: Five Factor Model of Personality (FFM); Liberal and conservative values; Linguistic analysis; Political preferences; dept.psy; peer-reviewed; “Populist” sentiment

Personality, Well-Being, and Cognitive-Affective Styles: A Cross-Sectional Study of Adult Third Culture Kids - Abe, Jo Ann A. (Journal of Cross-Cultural Psychology, 2018)
Third Culture Kids (TCKs) and their adult counterparts (ATCKs) refer to individuals who spent part of their developmental years abroad and are an important demographic to study in this rapidly globalizing world. To date, the bulk of the research on (A)TCKs has been descriptive and little is known about their developmental trajectories in adulthood. The major objective of this study was to examine the personality traits, dimensions of well-being, and cognitive-affective styles of ATCKs across the adult life span using well-validated psychological measures. A subsidiary goal was to develop a new multidimensional international experiences scale to assess levels of multicultural engagement in ATCKs. The participants in this study (N = 700+; age = 18-80+) were recruited from the Alumni Office of an international school in Japan. Somewhat contrary to how they are often depicted in the news media and in qualitative studies, the ATCKs showed normative changes in personality and well-being in the direction of greater maturity and adjustment during adulthood, with those reporting higher levels of multicultural engagement generally exhibiting a more resilient personality profile, higher levels of well-being, and more adaptive cognitive and affective styles.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-254-445-940-525 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: adult third culture kids; dept.psy; five-factor model of personality; need for closure; peer-reviewed; well-being

Influence of prenatal pre-exposure to an odor on intake behavior of an aversive solution in newborn rats. - Kamenetzky, Giselle V; Suarez, Andrea B; Ifran, Maria Celeste; Nizhnikov, Michael E; Pautassi, Ricardo M (Neuroscience letters, 2018)
Early pre- or postnatal sensory experiences significantly influence flavor preference and food intake, and can induce liking for innately unpalatable flavors. Previous work found that newborn rats stimulated with an odor experienced shortly after birth exhibited heightened intake and seeking towards an artificial nipple containing quinine. This result suggests that odors made familiar trough early postnatal pre-exposure can shift the motivational value of unconditional stimuli. The objective of the current study was to assess the effect of an odor (lemon) experienced in-utero on the first intake responses towards an artificial nipple supplying quinine. The hypothesis, which was corroborated, was that stimulation with the olfactory stimulus experienced in-utero would increase the newborn's intake and grasp responses to the artificial nipple containing quinine. Exposure to the odor that had been pre-exposed in utero increased quinine intake and seeking (i.e., latency to grasp and total time in contact with the nipple, as well as number of and mean duration of nipple grasps) in 3-h-old pups. These results replicate those previously found with postnatal odor pre-exposure, and extend the phase for pre-exposure to the prenatal stage. Copyright © 2018 Elsevier B.V. All rights reserved.
5 citations (Crossref) [2023-10-31] Place: Ireland Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Ifran, Maria Celeste. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: MariaCeleste.Ifran@Alumnos.uai.edu.ar. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, United States. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, C.P 5000, Argentina.
Keywords: *Eating; *Feeding Behavior; *Odorants; *Prenatal Exposure Delayed Effects; *Quinine/ad [Administration & Dosage]; Animals; Animals; Newborn; Animals; Suckling; Article; Eating; Feeding Behavior; Female; Male; Neonate rat; Odor pre-exposure; Odorants; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal exposure; Quinine; Rats; Sprague-Dawley; Smell; Sprague Dawley rat; animal; animal experiment; aversive agent; controlled study; dept.psy; eating; feeding behavior; female; food intake; fragrance; learning; male; newborn; nipple; nonhuman; odor; peer-reviewed; pregnancy; prenatal exposure; priority journal; quinine; rat; smelling; stimulation; suckling animal

Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H. (Journal of Fish Biology, 2018)
This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full-sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male-controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits. © 2018 The Fisheries Society of the British Isles
8 citations (Crossref) [2023-10-31]
Keywords: Animals; Female; Fertilization; Male; Mating Preference; Animal; Paternity; Perciformes; Reproduction; Sexual Behavior; Animal; Symphodus ocellatus; animal; behaviour; dept.psy; female; fertilization; male; mate choice; mating systems; paternity; peer-reviewed; reproduction; sexual behavior; sexual conflict; sexual selection; trade-offs

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
58 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-625-507-666-259, pop00148 tex.type: [object Object]
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Electrophysiological Indices of Audiovisual Speech Perception: Beyond the McGurk Effect and Speech in Noise. - Irwin, Julia; Avery, Trey; Brancazio, Lawrence; Turcios, Jacqueline; Ryherd, Kayleigh; Landi, Nicole (Multisensory research, 2018)
Visual information on a talker's face can influence what a listener hears. Commonly used approaches to study this include mismatched audiovisual stimuli (e.g., McGurk type stimuli) or visual speech in auditory noise. In this paper we discuss potential limitations of these approaches and introduce a novel visual phonemic restoration method. This method always presents the same visual stimulus (e.g., /ba/) dubbed with a matched auditory stimulus (/ba/) or one that has weakened consonantal information and sounds more /a/-like). When this reduced auditory stimulus (or /a/) is dubbed with the visual /ba/, a visual influence will result in effectively 'restoring' the weakened auditory cues so that the stimulus is perceived as a /ba/. An oddball design in which participants are asked to detect the /a/ among a stream of more frequently occurring /ba/s while either a speaking face or face with no visual speech was used. In addition, the same paradigm was presented for a second contrast in which participants detected /pa/ among /ba/s, a contrast which should be unaltered by the presence of visual speech. Behavioral and some ERP findings reflect the expected phonemic restoration for the /ba/ vs. /a/ contrast; specifically, we observed reduced accuracy and P300 response in the presence of visual speech. Further, we report an unexpected finding of reduced accuracy and P300 response for both speech contrasts in the presence of visual speech, suggesting overall modulation of the auditory signal in the presence of visual speech. Consistent with this, we observed a mismatch negativity (MMN) effect for the /ba/ vs. /pa/ contrast only that was larger in absence of visual speech. We discuss the potential utility for this paradigm for listeners who cannot respond actively, such as infants and individuals with developmental disabilities.
8 citations (Crossref) [2023-10-31] Place: Netherlands Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Avery, Trey. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA. Ryherd, Kayleigh. Haskins Laboratories, New Haven, CT, USA. Ryherd, Kayleigh. University of Connecticut, Storrs, CT, USA. Landi, Nicole. Haskins Laboratories, New Haven, CT, USA. Landi, Nicole. University of Connecticut, Storrs, CT, USA.
Keywords: Audio-visual speech; Audio-visual stimulus; Audiovisual; Audiovisual speech perception; Auditory stimuli; Developmental disability; ERP; Electrophysiology; Enterprise resource planning; Mismatch negativity; Phonemic restoration; Potential utility; Restoration; Speech; Speech recognition; Visual information; dept.psy; peer-reviewed; phonemic restoration